2009
DOI: 10.1016/j.jasms.2008.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of neuropeptides in crustacean hemolymph via MALDI mass spectrometry

Abstract: Neuropeptides are often released into circulatory fluid (hemolymph) to act as circulating hormones and regulate many physiological processes. However, the detection of these low-level peptide hormones in circulation is often complicated by high salt interference and rapid degradation of proteins and peptides in crude hemolymph extracts. In this study, we systematically evaluated three different neuropeptide extraction protocols and developed a simple and effective hemolymph preparation method suitable for MALD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 26 publications
1
57
0
Order By: Relevance
“…It is worth noticing that only 7 out of the 22 NPs also have decent matches with Mascot database searching, which may indicate that PEAKS is more suitable for identification of smaller NPs. As a result of improved instrumentation, more NPs were identified compared to a previous study using a similar sample preparation procedure with a modest resolution MALDI TOF/TOF instrument 12 . Out of these identified NPs, only CCAP and I/LNFTHKFa were detected in both studies.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…It is worth noticing that only 7 out of the 22 NPs also have decent matches with Mascot database searching, which may indicate that PEAKS is more suitable for identification of smaller NPs. As a result of improved instrumentation, more NPs were identified compared to a previous study using a similar sample preparation procedure with a modest resolution MALDI TOF/TOF instrument 12 . Out of these identified NPs, only CCAP and I/LNFTHKFa were detected in both studies.…”
Section: Resultsmentioning
confidence: 95%
“…Its presence in the decapod crustacean nervous system has been revealed by a number of MS studies 7, 24, 41 . Its presence in circulating hemolymph has also been confirmed 12 . Its canonical function is to stimulate cardiac activity 45 , although it is also active in the STNS 46 .…”
Section: New Insights Into Well-characterized Neuropeptidesmentioning
confidence: 83%
See 2 more Smart Citations
“…Curiously, however, despite stimulation of descending projection neurons both in vitro (Nusbaum and Beenhakker, 2002) and in vivo (Diehl et al, 2013;Hedrich et al, 2011) resulting in clear changes of CPG activity, most reported in vivo data show only the canonical motor patterns typically observed in unperturbed in vitro preparations (Hedrich et al, 2011;Massabuau and Meyrand, 1996;Clemens et al, 1998b). This is in spite of there being clear changes in the STG motor output in vitro Marder and Calabrese, 1996) and in vivo (Heinzel, 1988) in response to application of modulators known to be present in the blood (Li et al, 2002;Chen et al, 2009). It is unclear how prevalent in vivo modulation actually is, how it affects the long-term activity of the STG motor patterns and if the same variability of motor output reported in vitro exists under natural conditions.…”
Section: Introductionmentioning
confidence: 98%